The d-bar Neumann Problem and Schrödinger Operators - Haslinger, Friedrich (De Gruyter Expositions in Mathematics, 2014)
The topic of this book is located at the intersection of complex analysis, operator theory and partial differential equations.It begins with results on the canonical solution operator to restricted to Bergman spaces of holomorphic d-bar functions in one and several complex variables.These operators are Hankel operators of special type.